Pigmented trichoblastoma on sebaceous nevus. Review of the literature. - Ingravallo, G. (European Journal of Pediatric Dermatology, 2023)
Sebaceous nevus is an acquired mosaicism caused by activating mutations of oncogenes, particularly of the RAS family. This is the reason why tumors, which are benign in the majority of cases, can develop on sebaceous nevus. Trichoblastoma and syringocystadenoma papilliferum are the most frequent benign tumors arising on sebaceous nevus. In the current report, the case of a child with pigmented trichoblastoma arising on a sebaceous nevus was discussed and a review of the six similar cases in the literature was carried out.